2009
DOI: 10.1038/bmt.2009.236
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pretransplant comorbidities on alemtuzumab-based reduced-intensity conditioning allogeneic hematopoietic SCT for patients with high-risk myelodysplastic syndrome and AML

Abstract: We report a retrospective analysis of 128 consecutive patients with high-risk myelodysplastic syndrome (MDS) and AML who received an alemtuzumab-based reducedintensity conditioning hematopoietic SCT (RIC HSCT). The median recipient age was 53 years (range 21-72 years). A total of 49 (38%) recipients had a sibling donor and 79 (62%) had a volunteer-unrelated donor. The hematopoietic cell transplantation-specific comorbidity index (HCT-CI) was assigned to all patients with a score of 0 in 40 (31%), of 1-2 in 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…The 3-year outcomes of the IntermRIC regimens in the current study are in line with those found in prior studies (after excluding patients in an advanced disease status). 4,16,19,[32][33][34][35] In addition, long-term follow-up of the most common NMA protocol (Fludarabine þ 200 cGy TBI 36 ) in patients with AML in first or second CR reported a 6-year relapse incidence of 62%, a 27% PFS and an OS of 29%, similar to our cohort of NMA recipients. 37 Long-term comparative outcomes of various conditioning regimen intensities for AlloHSCT in AML and poor-risk MDS are not available to date.…”
Section: Discussionsupporting
confidence: 51%
“…The 3-year outcomes of the IntermRIC regimens in the current study are in line with those found in prior studies (after excluding patients in an advanced disease status). 4,16,19,[32][33][34][35] In addition, long-term follow-up of the most common NMA protocol (Fludarabine þ 200 cGy TBI 36 ) in patients with AML in first or second CR reported a 6-year relapse incidence of 62%, a 27% PFS and an OS of 29%, similar to our cohort of NMA recipients. 37 Long-term comparative outcomes of various conditioning regimen intensities for AlloHSCT in AML and poor-risk MDS are not available to date.…”
Section: Discussionsupporting
confidence: 51%
“…As comorbidities may have a significant negative influence on outcome after allogeneic HCT 23,24 evaluation of the HCT-CI 11 should be applied for comparison of results of the respective patient cohorts in different studies. In our study the HCT-CI was a median of 2.5, which is slightly higher than in other published studies and has to be kept in mind when comparing the OS rates.…”
Section: Discussionmentioning
confidence: 99%
“…While older age has been widely used to exclude patients from transplantation, assessment of comorbid conditions as measured by the hematopoietic cell transplantationspecific comorbidity index may help estimate risk of treatment-related mortality following HSCT [15][16][17]. In the presence of significant comorbidities, the danger of transplantation is far greater than postremission chemotherapy and may exclude patients from HSCT.…”
Section: Clinical Application Of Hsctmentioning
confidence: 99%